KAJIAN PENGOLAHAN PERMEN RUMPUT LAUT (Glacilaria Sp) DENGAN KONSENTRASI GULA YANG BERBEDA TERHADAP TINGKAT PENERIMAAN KONSUMEN - Aryani Aryani (Fish Scientiae, 2013)
This study research the effect of sugar adding on seaweed processing with the different concentration on consumer acceptance fase. Contribute from this research are to know the optimal sugar concentrate on processing seaweed candy. This research use 4 (four) treatments are the sugar adding concentrate 25 gram, 50 gram,75 gram and 100 gram. Result is showing that the different sugar concentrate adding are significant on water base and very significant effect on dust power and carbohydrate, which D is the best treatment.